Transmission of violet and blue light through conventional (layered) and bulk cured resin-based composites. (October 2016) - Harlow, J.E.; Rueggeberg, F.A.; Labrie, D.; Sullivan, B.; Price, R.B.
Abstract: Objectives: This study measured the transmission of light in the 'violet' (350 ≤ λ ≤ 425 nm) and 'blue' (425 < λ ≤ 550 nm) spectral ranges from a polywave ® LED curing light through different thicknesses of four commercial, resin-based composites (RBCs). Material and methods: Samples of conventional layered RBCs (Tetric EvoCeram A2, Filtek Supreme Ultra A2B), and bulk-curing resins (Tetric EvoCeram Bulk Fill IVA, and SureFil SDR Flow U) were prepared. Three samples of each RBC were made at thicknesses of 0.1, 0.7, 1, 2, and 4-mm. The uncured RBC specimens were affixed at the entrance aperture of a 6-inch integrating sphere and light-cured once for 20 s using a polywave ® LED curing light (Bluephase G2) on its high power setting. The spectral radiant power transmitted through each RBC in the 'violet' and 'blue' regions was measured using a fiberoptic spectrometer. Results: As RBC thickness increased, an exponential attenuation of transmitted light was measured (R 2  > 0.98). Attenuation was greater for the 'violet' than for the 'blue' spectral regions. At the light tip, the violet light component represented 15.4% of the light output. After passing through 4-mm of RBC, the violet light represented only between 1.2–3.1% of the transmitted light depending on the RBC. Depending on RBC, approximately 100 mW from the Bluephase G2 was transmitted through 0.1-mm of RBC in the 'violet' range, falling at most to 11 mW after passing through 2-mm of RBC, and to only 2 mW at 4-mm depth. Conclusions: Increasing RBC thickness results in an exponential decrease in light transmission. This attenuation is RBC-dependent with shorter wavelengths (violet) attenuated to a greater extent than longer wavelengths (blue). Clinical relevance: Despite the increased translucency of bulk curing RBCs, spectral radiant power shorter than 425 nm from a curing light is unlikely to be effective at a depth of 4-mm or more.